Gradient estimates for doubly nonlinear diffusion equations. (January 2015) - Chen, Daguang; Xiong, Changwei
Abstract: In this short note we obtain some gradient estimates for the positive solution to the doubly nonlinear diffusion equation on closed Riemannian manifold with Ricci curvature bounded below by a non-positive constant. As applications, we also derive corresponding Harnack inequalities.